2019
DOI: 10.21608/ajs.2019.12537.1027
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light Effects on Productive, Physiological Performance and Immune Response of Two Developed Laying Hens

Abstract: In this experiment, a total number of 165 birds (150 female + 15 male) from each developed laying hens Silver Montaza and Matrouh layer 20 weeks old up to 40 weeks of age. All bids were weighted and randomly distributed into 5 groups with three replicates per treatment (10 females and 1 male / replicate) with almost similar initial average body weight. Each experimental group was exposed to natural day light and supplemented with Ultraviolet light as in its program light, the main group (control group) exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The treatment exposed to UVB wavelength for5 hours increased live body weight compared to the LED group (control) or UVA5 and UVA10 in different ages, especially at 28 and 35 days, which the difference was significant among groups. The heaviest individuals weight were those exposed to UVB for 5 hours (2.594 kg), while the lowest individuals weight were those exposed to UVA for 10 hours (2.454 kg) at 35 day of age may be for beneficial effect of short time exposure for UV to activate some biochemical processes in the body and help for vitamin D production, while at long time exposure for UV often decreasing immune system efficient, this agreed with (Youssef et al 2019) who reported that influence of Ultraviolet radiation wavelength on environment surrounding the birds leads to improve immune system without a harmful effect in birds. Figure 1showed the live body weight during different periods of feeding (Starter, grower and finisher diets).…”
Section: Growth Performancesupporting
confidence: 61%
“…The treatment exposed to UVB wavelength for5 hours increased live body weight compared to the LED group (control) or UVA5 and UVA10 in different ages, especially at 28 and 35 days, which the difference was significant among groups. The heaviest individuals weight were those exposed to UVB for 5 hours (2.594 kg), while the lowest individuals weight were those exposed to UVA for 10 hours (2.454 kg) at 35 day of age may be for beneficial effect of short time exposure for UV to activate some biochemical processes in the body and help for vitamin D production, while at long time exposure for UV often decreasing immune system efficient, this agreed with (Youssef et al 2019) who reported that influence of Ultraviolet radiation wavelength on environment surrounding the birds leads to improve immune system without a harmful effect in birds. Figure 1showed the live body weight during different periods of feeding (Starter, grower and finisher diets).…”
Section: Growth Performancesupporting
confidence: 61%